Changes in groundwater recharge under projected climate in the upper Colorado River basin. Issue 13 (8th July 2016) - Tillman, Fred D; Gangopadhyay, Subhrendu; Pruitt, Tom
Abstract: Understanding groundwater‐budget components, particularly groundwater recharge, is important to sustainably manage both groundwater and surface water supplies in the Colorado River basin now and in the future. This study quantifies projected changes in upper Colorado River basin (UCRB) groundwater recharge from recent historical (1950–2015) through future (2016–2099) time periods, using a distributed‐parameter groundwater recharge model with downscaled climate data from 97 Coupled Model Intercomparison Project Phase 5 climate projections. Simulated future groundwater recharge in the UCRB is generally expected to be greater than the historical average in most decades. Increases in groundwater recharge in the UCRB are a consequence of projected increases in precipitation, offsetting reductions in recharge that would result from projected increased temperatures. Key Points: Flow in the Colorado River and tributaries is sustained by groundwater during low‐flow periods Mean daily temperature and precipitation are both projected to increase in the UCRB Simulated groundwater recharge in the UCRB is projected to be mostly above the historical average through 2099